The Role of Islamic Thought in the Development of World Civilization - Zaeni, Akhmad (International Journal of Islamicate Social Studies, 2023)
World civilization as time goes by continuously experiences a development. Various forms of thought or civilization that developed had an impact on the progress of existing civilizations. What is then interesting to discuss is how the contribution of Islamic thought to the development of world civilization. The question is the basis of this research. The method used in this study is descriptive qualitative with an interpretive approach. The conclusion in this study is that Islamic thought made a huge contribution to world civilization through mainland Europe. This is evidenced by the existence of various Muslim figures with each of his thoughts. Both relating to astronomy, medicine, exact science, and natural science or social science include philosophy and theology, social science. The contribution of Islamic thought is also given in various fields of life such as politics, economy, and social.